6. Pentavalent Meningococcal (MenABCWY) Vaccine is Safe and Well Tolerated With Immunogenicity Noninferior to Coadministered MenB-FHbp and MenACWY-CRM in a Phase 2 Study of Healthy Adolescents and Young Adults. (31st December 2020) - Peterson, James; Drazan, Daniel; Czajka, Hanna; Maguire, Jason; Pregaldien, Jean-Louis; Seppa, Ilkka; Maansson, Roger; O'Neill, Robert; Anderson, Annaliesa S; Balmer, Paul; Beeslaar, Johannes; Perez, John L
Abstract: Background: Meningococcal serogroups A, B, C, W and Y cause nearly all meningococcal disease globally. Vaccination is complicated by different dosing recommendations for serogroup B (MenB) and quadrivalent (MenACWY) vaccines, which could be solved with a single pentavalent vaccine. This study in adolescents and young adults evaluated a new pentavalent MenABCWY vaccine that combines 2 licensed vaccines, MenB-FHbp (Trumenba ® ; bivalent rLP2086) and MenACWY-TT (Nimenrix ® ), into a single vaccine. Methods: In this ongoing, randomized, controlled, observer-blinded, multicenter study (NCT03135834), MenB vaccine-naive and MenACWY-naive or -experienced healthy 10–25-year-olds were randomized 1:2 to MenABCWY (Month 0, 6) or MenB-FHbp (Month 0, 6) and MenACWY-CRM (Month 0). Immune responses were measured by serum bactericidal activity assays with human complement (hSBA) against serogroup A, C, W and Y strains and 4 diverse, vaccine-heterologous MenB strains. Endpoints included percentages of subjects achieving ≥ 4-fold rises in titers from baseline. Noninferiority of immune responses was assessed at the 10% margin (95% CI lower limit > −10%). Safety was assessed. Results: Following dose 2, high percentages of MenABCWY (n=543) and MenB-FHbp (n=1057) recipients achieved ≥ 4-fold rises against each of the 4 MenB strains (75.8−94.7% vs 67.4−95.0%) and titers reaching at least the lower limit of quantification against all 4 strains combined (79.9% vs 74.3%; Figure 1A ). MenABCWY was noninferior to MenB-FHbp for all 5 endpoints. MenABCWY was also noninferior to a single MenACWY-CRM dose with 75.5−96.9% and 93.0−97.4% of MenABCWY recipients after dose 1 or 2, respectively, achieving ≥ 4-fold rises against serogroup A, C, W and Y depending on prior MenACWY experience (Figure 1B ). Local reactions and systemic events after MenABCWY or MenB-FHbp were similarly frequent, mostly mild/moderate in severity (Figure 2 ), and unaffected by MenACWY experience. Figure 1. Immune Responses as Measured in hSBA to (A) MenB Test Strains at 1 Month After Dose 2 and (B) MenA, MenC, MenW, and MenY Test Strains at 1 Month After Doses 1 and 2 Figure 2. (A) Local Reactions and (B) Systemic Events Reported Within 7 Days After Any Dose Conclusion: MenABCWY 4-fold immune responses from baseline were robust and noninferior to MenB-FHbp and MenACWY-CRM administered separately. Vaccination was safe and well tolerated. The favorable benefit-risk profile supports further MenABCWY development as a simplified alternative to current meningococcal vaccination practices. Funded by Pfizer. Disclosures: James Peterson, MD, Pfizer (Scientific Research Study Investigator) Daniel Drazan, MD, Pfizer (Scientific Research Study Investigator) Hanna Czajka, MD, PhD, Pfizer (Scientific Research Study Investigator) Jason Maguire, MD, Pfizer (Employee, Shareholder) Jean-Louis Pregaldien, MS, Pfizer (Employee, Shareholder) Ilkka Seppa, MD, Pfizer (Scientific Research Study Investigator) Roger Maansson, MS, Pfizer (Employee, Shareholder) Robert O'Neill, PhD, Pfizer (Employee, Shareholder) Annaliesa S. Anderson, PhD, Pfizer (Employee, Shareholder) Paul Balmer, PhD, Pfizer Inc (Employee, Shareholder) Johannes Beeslaar, MD, Pfizer (Employee, Shareholder) John L. Perez, MD, MA, Pfizer Inc (Employee, Shareholder)